INFLUENCE OF SOLVENT POLARITY ON ULTRASOUND-ASSISTED EXTRACTION OF RUBBER SEED OIL: YIELD, CHEMICAL COMPOSITION, AND PHYSICOCHEMICAL CHARACTERISTICS - Imalia, Calaelma Logys; Saputri, Desi Riana; Damayanti, Damayanti; Auriyani, Wika Atro; Alhanif, Misbahudin; Fahni, Yunita; Sanjaya, Andri; Achmad, Feerzet; Deviany, Deviany; Sufra, Rifqi; Safitra, Edwin Rizki; Sanjaya, Bagus Gelorawan; Sari, Dewi Kurnia (JURNAL INTEGRASI PROSES, 2025)
Rubber seeds contain fatty acids that can be used as industrial mixtures and processed into biodiesel, soap production, and animal feed. So far, the utilization of rubber seeds has not been optimal, so rubber seeds can be processed into oil using an ultrasound-assisted extraction (UAE). The study aimed to determine the characteristics of oil from rubber seed extract, such as color, odor, and chemical compound content. In addition, the study seeks to assess the effect of solvent type (n-hexane, ethyl acetate, and ethanol), extraction time (30, 45, and 60 minutes), and ratio of material :solvent (1:5, 1:6, and 1:7 w/v) on the yield (%) of oil extract from rubber seeds. The results showed that oil from rubber seed extract obtained with n-hexane exhibited a yellow color and had a rubber seed aroma, ethyl acetate solvent produced a cloudy yellow color and had an ethyl acetate aroma, and ethanol solvent produced a brownish yellow color and had a rubber seed aroma. The most significant oil extraction result from rubber seeds is ethanol solvent with a time of 45 and 60 minutes, and a ratio of material to solvent of 1:7 w/v. The rubber seed oil content was tested using GC-MS taken from the three best samples of each type of solvent (n-hexane, ethyl acetate, and ethanol) at an extraction time of 45 minutes and a ratio of material to solvent of 1:7 w/v. The oil compound content in rubber seed extract was 90.64% using hexane, 35.95% using ethyl acetate, and 25.19% using ethanol as solvents. The oil compounds extracted using n-hexane solvent consisted of 9-octadecanoic acid, methyl ester at 63.917%, those using ethyl acetate solvent were acetic acid, butyl ester at 30.67%, and those using ethanol solvent were n-hexadecanoic acid at 9.15%.